La dimension européenne de la libéralisation des terres et les réformes agraires du milieu du 18e siècle au début du 19e - Jessenne, Jean Pierre; Vivier, Nadine (2021)
This paper, a summary of current knowledge, aims at showing the widespread aspirations for agrarian reforms in Enlightenment Europe. It goes beyond the compartmentalization of national historiographies and focuses on the intense exchange of ideas and agronomic experiences. The reforms of farm ownership methods are inseparable from reflections on political economy and social organization. The first attempts at reform in the years 1760-1780 gave rise to strong social tensions and divergent reactions from European states. The French Revolution was agitated by strong contradictions, and it resulted in a form of moderate agrarian liberalism. It left its mark on Europe, without imposing a model, it rather contributed to accentuating national differentiations: while some countries carried on their reforms, others embraced a conservative reaction.
Cet article de synthèse veut dépasser le cloisonnement des historiographies nationales pour montrer l'importance des aspirations aux réformes agraires, celles des modes de propriété et d'exploitation de la terre. Dans l'Europe des Lumières, les échanges d'idées et d'expériences agronomiques sont intenses, ils sont indissociables des réflexions sur l'économie politique et l'organisation sociale. Les premières tentatives de réformes, dans les années 1760-1780 suscitent de fortes tensions sociales et des réactions divergentes des Etats européens. La Révolution française agitée par de fortes contradictions, imprime sa marque : elle aboutit à une forme de libéralisme agraire mitigé. Sans imposer un modèle à l'Europe, elle contribue plutôt à accentuer les différenciations nationales : alors que certains pays continuent leurs réformes, d'autres ont une réaction conservatrice.
Keywords: Enlightenment Europe; French Revolution; Agronomic exchanges; Liberalism; Agrarian reforms; Europe des Lumières^lfr; Révolution française; Échanges agronomiques; Libéralisme; Réformes agraires